EFFECTS OF TEMPERATURE AND IONIC STRENGTH ON THE STABILITIES OF THE FIRST AND SECOND FLUORIDE COMPLEXES OF YTTRIUM AND THE RARE EARTH ELEMENTS - Luo Y.; Millero F.J. (My University, 2004)
The stability constants for the formation of yttrium and rare earth elements (YREEs) with fluoride(A1)Ln3++F−↔LnF2+β1F (A2)Ln3++2F−↔LnF2+β2+F have been determined by an ion exchange method in dilute solutions as a function of temperature (5 to 45°C). The concentrations of the YREEs were measured using ICP- mass spectrometry. The values of log β1 and log β2 at 25.0°C are in good agreement with the work of Schijf and Byrne (1999). The effect of temperature on the stability constants has been used to determine the enthalpies of formation of LnF2+ and LnF2+. Average values of ΔH1 = +9.6 ± 0.4 kJ/mol and ΔH2 = +20.7 ± 1.1 kJ/mol were found for the enthalpies. Our results are in reasonable agreement with literature values of ΔH1 (Paul et al., 1961; Baisden et al., 1987; Grant et al., 1988). The measurements from Luo and Byrne (2000, 2001) for the formation of LnF2+ as a function of ionic strength in NaCl and NaClO4 have been fitted to the Pitzer equations. These results have been used to examine the effect of ionic strength on the activity coefficients of the LnF2+ ions in NaCl and NaClO4 solutions. At low ionic strengths the activity coefficients of LnF2+ for the YREEs are independent of atomic number. Since the values of ΔH1 do not appear to be a strong function of ionic strength, these results can be used to estimate the stability constants for the formation of LnF2+ complexes from 0 to 50°C and I = 0 to 6 m.